Educational and educational issues in a global climate. (Open Herald: Periodical of Methodical Research, 2024)
The article analyzed issues related to ensuring the spiritual safety of young people as a separate research object at a time when globalization processes are intensifying. The issue of developing the spirituality of young people and serving as an important factor in the development of knowledge and spiritual values is reflected in the sustainable development of our country